The role of the family caregiver as a special life experience - Janowicz, Anna (Difficult situation in biographies: Volume 9, 2025)
People play different social roles in their lives. Among them there is the role of a caregiver of a sick loved one, who requires long-term care. It brings to their biography many different experiences, challenges, emotions, consequences… It is sometimes undertaken overnight, without the possibility of preparing for it, and sometimes gradually, with increasing commitment over time and the growing needs of the mentee. Care in the family system is strongly rooted in Polish tradition. Still insufficiently supported by formal care systems, it entails many burdens for which they must find solutions and provide appropriate assistance. This becomes particularly important at a time of ageing society, decreasing family care potential and the process of deinstitutionalisation of care services. In this case, each individual story of a family caregiver becomes an important element of the functioning of the community and society in various dimensions and contexts.